Pendampingan Keselamatan Dan Kesehatan Kerja Petugas Sampah di Desa Tamanharjo, Singosari Malang - Yoyok Bekti Prasetyo; Rahmad Wijaya; Joko Susilo (University of Muhammadiyah Malang, 2021)
Garbage workers are very at risk of accidents at work. The work environment of the waste officer when handling garbage in the trash can which has a lot of sharp and dangerous objects, bringing various types of diseases. Efforts are needed to assist waste officers. This assistance is carried out by providing health education about the risks and dangers of the diseases that can be experienced by waste officers while working. This assistance is a promotive and preventive effort aimed at waste officers to avoid health problems or occupational diseases. Most of the work accidents experienced by garbage officers were due to mechanical factors such as being scratched, stabbed, and slipping (71.4%). Another accident was twisted and a falling by 42.9% for each. Meanwhile, for occupational diseases, musculoskeletal problems (pain in the waist muscles) and the presence of conflict were higher, namely 42.9% compared to diarrhea and itching of the skin, namely 14.3%. Health education on occupational safety and health for waste officers is effective in increasing the knowledge of waste officers about the risks of their work environment.